1996
DOI: 10.1007/bf01466628
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical analysis of joint contact forces in the posterior cruciate deficient knee

Abstract: The approach to the posterior cruciate deficient knee is controversial. The purpose of this study is to document the biomechanical changes in the static cadaveric knee model with simulated physiological loads. Nine fresh cadaveric knees from young donors (aged under 45 years) were mounted on a materials testing machine. Loading was carried out at 0 degrees, 30 degrees and 60 degrees to 1.5 kN with low-pressure sensitive Prescale film (Fuji; Tokyo, Japan) inserted through arthrotomies into the medial and latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 16 publications
4
31
0
1
Order By: Relevance
“…It is now generally accepted that patients with isolated PCL injuries with greater than 10 mm of posterior laxity or high-grade PCL injuries associated with multiligamentous knee injuries have improved subjective outcomes, side-to-side differences in stability, and decreased laxity on stress radiographs with operative intervention [5,11,13,23,25,36,39,45,47,54]. This may be the result of restoration of normal knee kinematics and a decreased propensity to develop medial compartment and patellofemoral compartment arthrosis [7,19,26,28,46,51]. Despite the demonstrated benefit of operative intervention, debate remains over the most advantageous operative technique.…”
Section: Introductionmentioning
confidence: 99%
“…It is now generally accepted that patients with isolated PCL injuries with greater than 10 mm of posterior laxity or high-grade PCL injuries associated with multiligamentous knee injuries have improved subjective outcomes, side-to-side differences in stability, and decreased laxity on stress radiographs with operative intervention [5,11,13,23,25,36,39,45,47,54]. This may be the result of restoration of normal knee kinematics and a decreased propensity to develop medial compartment and patellofemoral compartment arthrosis [7,19,26,28,46,51]. Despite the demonstrated benefit of operative intervention, debate remains over the most advantageous operative technique.…”
Section: Introductionmentioning
confidence: 99%
“…The larger curvature radius of the medial femoral condyle means that with relative anterior subluxation of the femur; a higher pressure point with less congruence occurs at the tibiofemoral joint entrapping the anterior portion of the medial meniscus [49]. The pattern of the articular cartilage degeneration and meniscal injury correlates with the abnormal kinematics and contact pressures in the medial compartment of the PCL deficient knee demonstrated in cadaveric studies as outlined above [6,44].…”
Section: The Impact Of Altered Kinematics Of Pcl Injury On Long Term mentioning
confidence: 91%
“…One study reported a significant increase at 60 and 90°of flexion but no changes at 0 and 30°of flexion [6]. Another study reported a mean increase of 52% of medial compartment pressure regardless of flexion angle [44].…”
Section: Cadaveric Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…19 Further, several studies have shown that PCL insufficiency leads to a significant increase in pressure to the medial compartment. 20,21 A most common mechanism of isolated PCL injury is the dashboard injury, either in trauma, when a flexed knee hit the dashboard, or in sports activities, when the knee hits the ground, pushing the tibia backwards. 22 Hyperflexion or hyperextension of the knee could also give rise to PCL injuries.…”
Section: Posterior Cruciate Ligamentmentioning
confidence: 99%